Four new species of Ciulfina Giglio-Tos, 1915 (Mantodea: Liturgusidae, Liturgusinae) from the Northern Territory, Australia - Holwell, Gregory I. (Zootaxa, 2014)
The praying mantid genus Ciulfina Giglio-Tos includes many small, gracile tree-trunk dwelling species found throughout northern Australia. Four new species of Ciulfina: C. annecharlotteae, C. herbersteinae, C. ianrichardi, and C. terrymariceae are formally described on the basis of male genital morphology.